Fiqh of Artificial Intelligence in a Quranic Perspective: Normative Framework for the Use of AI in the Religious Sphere - Salleh Mohammed Habeebullah; Syarifah Wahyuni; Nur Afifah Ekowati; Mussa Otim (Yayasan Albahriah Jamiah Indonesia, 2026)
The increasingly intensive use of artificial intelligence in religious practices—such as the interpretation of religious texts, digital fatwā, and prayer assistance—raises serious normative issues related to the authority of knowledge, legal legitimacy, and the boundaries of the relationship between humans and technology in Islam. So far, studies of AI fiqh have been dominated by pragmatic approaches and partial legal analogies, and have not systematically departed from the normative foundations of the Quran as the primary source of Islamic law. This study aims to formulate a principled-conceptual normative framework for artificial intelligence fiqh, grounded in the Quran, for assessing the use of AI in the religious sphere. This study employs a normative legal method, with a thematic interpretation (mawḍūʻī) approach, to examine Quranic verses on reason, knowledge, trust, moral responsibility, and the relationship between humans and technology. A critical conceptual analysis of classical and contemporary fiqh literature accompanies it. The results show that the normative framework for AI fiqh can be formulated based on three main findings. First, ontologically, AI is positioned as an instrument resulting from human endeavor, not a moral subject or a source of normative authority. Second, epistemologically, AI is limited to analytical and computational support functions in the production of religious knowledge, without replacing ethically and legally responsible human reasoning. Third, normatively, the use of AI must comply with the moral principles of the Quran, including justice, benefit, accountability, and prevention of harm. In conclusion, this study offers a conceptual contribution in the form of a normative framework for AI fiqh that affirms the supremacy of the Quran as the primary reference for responding to the transformation brought about by cutting-edge technology, while strengthening the foundation of contemporary fiqh in facing digital challenges.